PEMIKIRAN DELIAR NOER MENGENAI GERAKAN ISLAM MODERN INDONESIA 1900-1942 - Iskandar, Irpan; Firdaus, Dede Wahyu (Jazirah: Jurnal Peradaban dan Kebudayaan, 2020)
Deliar Noer is Indonesian scholar in the field of Islamic politics and history in 20th century. His thoughts on the modern Indonesian Islamic movement 1900-1942 have made scientific contributions and become a reference for Islamic studies in Indonesia. The writing of this article aims to analyze the thoughts of a Deliar Noer in his book entitled "Modern Indonesian Islamic Movement 1900-1942". The method used in thi article is a literature review research method. The results showed; (1) the beginning ofthe modern Islamic movement emerged from the influence of the ulama who studied in the Middle East, until modern Islamic thoughts spread to various regions in the Dutch East Indies using organizational, educational, and press methods. (2) Modern Islamic movements in Indonesia can be distinguished into social education, political and economic movements. (3) the development of the modern Islamic movement experienced dynamics and reactions that emerged from the Dutch colonial government, traditional Muslim circles, as well as national and nationalist circles.